Identifikasi Senyawa Kimia dalam Buah Mahkota Dewa (Phaleria macrocarpa), Thymelaceae - PARTOMUAN SIMANJUNTAK (JURNAL ILMU KEFARMASIAN INDONESIA, 2008)
Consecutive extraction of Indonesian medicinal plant, fruit of mahkota dewa, Phaleria macrocarpa (Thymelaceae), by n-hexane, aethylacetate, methanol and then Water afforded fatty acids, steroids, benzophenone and carbohydrate. Elucidation of the chemical structure of the isolated compounds was based upon the spectroscopic spectra such as ultra violet, infrared, and nuclear magnetic resonance (proton and carbon).